Access control list configuration to block anti-censorship software in higher education institutions in Malaysia - Osman, Baharudin; Abas, Azizi; Ghazali, Osman; Harmoni, Kamal (Universiti Utara Malaysia Press, 2012)
Anti-censorship software was originally developed to fight internet censorship in China.A anti-censorship software such as UltraSurf, Freegate, Gpass, GTunnel and FirePhoenix became popular with stubborn users who used the Internet for thier own purposes and disobeyed the organization’s policies.Statistics show that Facebook, and YouTube are ranked as the most popular websites used by college students in Malaysia.Since they are widely used by users in the local area network to bypass firewall policies, they have become a threat to the LAN organization.Hence, it causes a problem for network administrators who manage internet utilisation and enforce internet policies.For an organisation, uncontrolled internet usage leads the open system to be vulnerably to viruses, backdoor,non productivity activities and slow internet connections. Thus, this study proposes a strategy to filter and block traffic created by anti-censorship software in LAN.The method used in this project is the “design computer security experiment”.Therefore, this project will guide the network administrator to control internet utilisation, protect the organisation’s LAN and carry out the implementation of the internal organization’s internet policies.As a result, this paper has proposed a strategy to block the UltraSurf anti-censorship software.The proposed strategy was tested in several public and private higher education institutions.